Diagnostic accuracy of the Cobas 6800 RT-PCR assay for detection of SARS-CoV-2 RNA - Mahmoud, Sally; Ganesan, Subhashini; Raheja, Preety; Cantarutti, Flavia; Ateia, Hagar; Zaher, Walid (Frontiers in Analytical Science, 2022)
Introduction: The COVID-19 pandemic has led to the rapid development and launch of several commercial RT-PCR-based assays for identification of SARS-CoV-2. However, there is need for peer-reviewed evaluation of these assays that can support their clinical performance. In this study, we, therefore, conduct an in-house evaluation of the automated Cobas 68000 RT-PCR assay in detecting SARS-CoV-2 infections using different pooling techniques. Methods: An observational study is conducted to evaluate the clinical performance of the Cobas 6800 SARS-CoV-2 assay in comparison with the Labgun Exofast RT-PCR kit, using both pooled and non-pooled sample techniques. A total of 300 nasopharyngeal swab samples, 40 known positive samples and 260 negative samples, are used for pooling, while the performance is evaluated in three different sample pool sizes of 4, 5, and 6. Results: The sensitivity and specificity of the Cobas 6,800 was 100% when compared to the comparable assay. The sample pooling technique showed that specificity was 100% in all pool sizes and the sensitivity varied from 95% in the 6-pooled sample to 100% in both the 5- and 4-pooled samples. The lower limit of detection was verified as 25 copies/ml for un-pooled samples, and, therefore, the limit of detection was 100, 125, and 150 copies/ml for the 4, 5, and 6 sample pools, respectively. Strong correlation was observed between the Ct values of the target genes of both assays. Conclusion: Cobas 6800 RT-PCR assay is a reliable platform for qualitative and rapid detection of SARS-CoV-2 and can be effectively utilized for pooling of samples with highly efficient performance when disease prevalence is lower.